Comparison of photo- and thermally initiated polymerization-induced self-assembly: a lack of end group fidelity drives the formation of higher order morphologies. Issue 18 (19th April 2017) - Blackman, Lewis D.; Doncom, Kay E. B.; Gibson, Matthew I.; O'Reilly, Rachel K.
Abstract : We demonstrate that the PISA of identical block copolymers by either a photo or thermally initiated approach leads to structures that are both chemically and morphologically distinct. Abstract : Polymerization-induced self-assembly (PISA) is an emerging industrially relevant technology, which allows the preparation of defined and predictable polymer self-assemblies with a wide range of morphologies. In recent years, interest has turned to photoinitiated PISA processes, which show markedly accelerated reaction kinetics and milder conditions, thereby making it an attractive alternative to thermally initiated PISA. Herein, we attempt to elucidate the differences between these two initiation methods using isothermally derived phase diagrams of a well-documented poly(ethylene glycol)- b -(2-hydroxypropyl methacrylate) (PEG- b -HPMA) PISA system. By studying the influence of the intensity of the light source used, as well as an investigation into the thermodynamically favorable morphologies, the factors dictating differences in the obtained morphologies when comparing photo- and thermally initiated PISA were explored. Our findings indicate that differences in a combination of both reaction kinetics and end group fidelity led to the observed discrepencies between the two techniques. We find that the loss of the end group in photoinitiated PISA drives the formation of higher order structures and that a morphological transition from worms to unilamellar vesicles could be induced by extended periods of light and heat irradiation. Our findings demonstrate that PISA of identical block copolymers by the two different initiation methods can lead to structures that are both chemically and morphologically distinct.